The Demographic History of Populations and Genomic Imprinting have Shaped the Transposon Patterns in Arabidopsis lyrata - Padilla-García, Nélida; Le Veve, Audrey; Čermák, Vojtěch; İltaş, Ömer; Contreras-Garrido, Adrián; Legrand, Sylvain; Aury, Jean-Marc; Horvath, Robert; Lafon Placette, Clément (Molecular biology and evolution, 2025)
Purifying selection is expected to prevent the accumulation of transposable elements (TEs) within their host, especially when located in and around genes and if affected by epigenetic silencing. However, positive selection may favor the spread of TEs, causing genomic imprinting under parental conflict, as genomic imprinting allows parent-specific influence over resource accumulation to the progeny. Concomitantly, the number and frequency of TE insertions in natural populations are conditioned by demographic events. In this study, we aimed to test how demography and selective forces interact to affect the accumulation of TEs around genes, depending on their epigenetic silencing, with a particular focus on imprinted genes. To this aim, we compared the frequency and distribution of TEs in Arabidopsis lyrata from Europe and North America. Generally, we found that TE insertions showed a lower frequency when they were inserted in or near genes, especially TEs targeted by epigenetic silencing, suggesting purifying selection at work. We also found that many TEs were lost or got fixed in North American populations during the colonization and the postglacial range expansion from refugia of the species in North America, as well as during the transition to selfing, suggesting a potential "TE load." Finally, we found that silenced TEs increased in frequency and even tended to reach fixation when they were linked to imprinted genes. We conclude that in A. lyrata, genomic imprinting has spread in natural populations through demographic events and positive selection acting on silenced TEs, potentially under a parental conflict scenario.
Keywords: molekulární evoluce; North America; Epigenesis, Genetic; transposable elements; populační genetika; Severní Amerika; Evolution, Molecular; Genetics, Population; Europe; Genomic Imprinting; Arabidopsis lyrata; transpozibilní elementy DNA; Arabidopsis; epigeneze genetická; positive selection; transposon load; genomový imprinting; DNA Transposable Elements; genomic imprinting; Evropa; selekce (genetika); Selection, Genetic; demographic history